LO88: S100B serum protein level for the detection of clinically significant intracranial hemorrhage in patients with mild traumatic brain injury: a prospective cohort study. (May 2020) - Blais-L'Écuyer, J.; Blais-L'Écuyer, J.; Mercier, É.; Tardif, P.; Archambault, P.; Chauny, J.; Berthelot, S.; Frenette, J.; Perry, J.; Stiell, I.; Émond, M.; Lee, J.; et al.
Abstract : Introduction: Clinical assessment of patients with mTBI is challenging and overuse of head CT in the emergency department (ED) is a major problem. During the last decades, studies have attempted to reduce unnecessary head CTs following a mTBI by identifying new tools aiming to predict intracranial bleeding. S100B serum protein level might be helpful reducing those imaging since a higher level of S-100B protein has been associated with intracranial hemorrhage following a mTBI in previous literature. The main objective of this study was to assess whether the S100B serum protein level is associated with clinically important brain injury and could be used to reduce the number of head CT following a mTBI. Methods: This prospective multicenter cohort study was conducted in five Canadian ED. MTBI patients with a Glasgow Coma Scale (GCS) score of 13-15 in the ED and a blood sample drawn within 24-hours after the injury were included. S-100B protein was analyzed using enzyme-linked immunosorbent assay (ELISA). All types of intracranial bleedings were reviewed by a radiologist who was blinded to the biomarker results. The main outcome was the presence of clinically important brain injury. Results: A total of 476 patients were included. Mean age was 41 ± 18 years old and 150 (31.5%) were female. Twenty-four (5.0%) patients had a clinically significant intracranial hemorrhage while 37 (7.8%) had any type of intracranial bleeding. S100B median value (Q1-Q3) of was: 0.043 ug/L (0.008-0.080) for patients with clinically important brain injury versus 0.039 μg/L (0.023-0.059) for patients without clinically important brain injury. Sensitivity and specificity of the S100B protein level, if used alone to detect clinically important brain injury, were 16.7% (95% CI 4.7-37.4) and 88.5% (95% CI 85.2-91.3), respectively. Conclusion: S100B serum protein level was not associated with clinically significant intracranial hemorrhage in mTBI patients. This protein did not appear to be useful to reduce the number of CT prescribed in the ED and would have missed many clinically important brain injuries. Future research should focus on different ways to assess mTBI patient and ultimately reduce unnecessary head CT.